Long-term analysis of prognostic risk factors impacting surgical outcomes in patients with external auditory canal carcinoma - Lohnherr, Vera; Wurzrainer, Niklas; Sand, Matthias; Federspil, Philippe; Heß, Jochen; Plath, Karim; Plath, Michaela (European archives of oto-rhino-laryngology and head & neck, 2023)
Malignant neoplasms of the external auditory canal (EAC) are rare. No consensus on management has emerged.
Online veröffentlicht: 20. Februar 2023
Gesehen am 19.09.2024